HSI-II Gene Cluster of Pseudomonas syringae pv. tomato DC3000 Encodes a Functional Type VI Secretion System Required for Interbacterial Competition - Chien, Ching-Fang; Liu, Cheng-Ying; Lu, Yew-Yee; Sung, You-Hsing; Chen, Kuo-Yau; Lin, Nai-Chun (Frontiers in Microbiology, 2020)
The type VI secretion system (T6SS) is a widespread bacterial nanoweapon used for delivery of toxic proteins into cell targets and contributes to virulence, anti-inflammatory processes, and interbacterial competition. In the model phytopathogenic bacterium Pseudomonas syringae pv. tomato (Pst) DC3000, two T6SS gene clusters, HSI-I and HSI-II, were identified, but their functions remain unclear. We previously reported that hcp2, located in HSI-II, is involved in competition with enterobacteria and yeast. Here, we demonstrated that interbacterial competition of Pst DC3000 against several Gram-negative plant-associated bacteria requires mainly HSI-II activity. By means of a systematic approach using in-frame deletion mutants for each gene in the HSI-II cluster, we identified genes indispensable for Hcp2 expression, Hcp2 secretion and interbacterial competition ability. Deletion of PSPTO_5413 only affected growth in interbacterial competition assays but not Hcp2 secretion, which suggests that PSPTO_5413 might be a putative effector. Moreover, PSPTO_5424, encoding a putative 54-dependent transcriptional regulator, positively regulated the expression of all three operons in HSI-II. Our discovery that the HSI-II gene cluster gives Pst DC3000 the ability to compete with other plant-associated bacteria could help in understanding a possible mechanism of how phytopathogenic bacteria maintain their ecological niches.